SOCIODEMOGRAPHIC INEQUALITIES IN THE AGE OF INTRODUCTION OF ULTRA-PROCESSED FOOD IN THE FIRST YEAR OF LIFE. THE CLAB-BRAZIL STUDY - Maiara Aparecida Mialich Almeida; Caroline de Barros Gomes; Michelly da Silva Alves; Maria Antonieta Barros Leite Carvalhaes (Universidade do Estado do Rio de Janeiro, 2019)
Introduction: Food inadequacies in the first year of life are considered a global problem, especially the introduction of extremely palatable ultra-processed foods (UPFs) with low nutritional value to infant diets. Objective: To identify sociodemographic differences related to the median age of introduction of UPFs in the first year of life in a cohort of infants. Methods: Prospective cohort study collecting data on the diet of 641 babies during their first year of life through face-to-face and telephone interviews. Socioeconomic and demographic data were obtained at the baseline. The UPFs were grouped according to their nature, composition and purpose of consumption. The median ages at onset of the UPF groups were estimated by Kaplan-Meier survival curves using the Log Rank test (Mantel-Cox) with p <0.05 as the critical value to determine significant differences in median ages according to sociodemographic variables. Results: Nonwhite mothers introduced sandwich cookies, snacks, and ultra-processed sweetened drinks 25 days earlier than white mothers; adolescents offered ultra-processed sweetened and ultra-processed dairy drinks 120 days earlier than adults. Absence of a partner led to the lowest median age of introduction of the "margarine and spreads" group. Primiparas introduced ultra-processed sweetened drinks, milk flours, children's cereals and powdered chocolate earlier, with a median age of 190 and 290 days, respectively. Conclusions: There were sociodemographic differences in the age of introduction of UPFs, with unfavorable results for infants whose mothers were non-white, adolescents, primiparous and did not live with a partner. DOI: 10.12957/demetra.2019.43615